The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1139/f98-093
|View full text |Cite
|
Sign up to set email alerts
|

Sperm motility patterns of Atlantic cod (Gadus morhua) in relation to salinity: effects of ovarian fluid and egg presence

Abstract: A significantly greater proportion of Atlantic cod (Gadus morhua) sperm were motile in the presence of ovarian fluid and egg compared with seawater. Sperm mean and maximum swimming speeds were also significantly greater in the presence of ovarian fluid and egg compared with seawater. However, there was no significant difference in path linearity among treatments. We also examined the interaction between maternal stimuli (egg and ovarian fluid), time sperm spent in seawater prior to exposure to each stimulus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 24 publications
8
68
3
Order By: Relevance
“…Salmonids are known to have one of the briefest fertile windows among fish and the period of sperm survival is short when observed in water (Vladic and Järvi, 1997, own observations). Yet, the ovarian fluid represents a protective environment (Litvak and Trippel, 1998) and Arctic charr ejaculates have a higher percentage of motile sperm cells in ovarian fluid than in water (Turner and Montgomerie, 2002). Moreover, the ovarian fluid seems to represent a selective environment for sperm (Yeates et al, 2013), and there is a strong interaction effect of ovarian fluid on sperm swimming speed in charr with certain female fluids stimulating swimming speed of sperm from some males over others (Urbach et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonids are known to have one of the briefest fertile windows among fish and the period of sperm survival is short when observed in water (Vladic and Järvi, 1997, own observations). Yet, the ovarian fluid represents a protective environment (Litvak and Trippel, 1998) and Arctic charr ejaculates have a higher percentage of motile sperm cells in ovarian fluid than in water (Turner and Montgomerie, 2002). Moreover, the ovarian fluid seems to represent a selective environment for sperm (Yeates et al, 2013), and there is a strong interaction effect of ovarian fluid on sperm swimming speed in charr with certain female fluids stimulating swimming speed of sperm from some males over others (Urbach et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The role that ovarian fluid plays in influencing motility and fertilization success has recently been studied (Litvak and Trippel, 1998). It was revealed that cod sperm motility is enhanced when diluted semen was placed in ovarian fluid or directly on the egg's surface still coated by ovarian fluid compared to seawater alone.…”
Section: Application Of Sperm Motility Data To Estimation Of Stockviamentioning
confidence: 99%
“…Eggs, ovarian fluid, sperm, seminal fluid and seawater become mixed when genital pores are closely aligned during spawning. The ovarian fluid contribution to the gamete mixture may improve chances for fertilization, such that sperm can be activated or their velocity enhanced when in contact with maternal substances (Amanze and Iyengar, 1990;Litvak and Trippel, 1998). Note, turbot sperm motility (duration) approximately doubled when males were kept in captivity with other females as compared to being in isolation (Suquet et al, 1992b) and a lengthier period of herring sperm motility occurred in the presence of eggs (Geffen, 1999).…”
Section: Application Of Sperm Motility Data To Estimation Of Stockviamentioning
confidence: 99%
“…Prior work in several fish species has shown that ovarian fluid, a viscous substance surrounding the spawned ova, enhances sperm longevity, per cent motility, path linearity and sperm velocity compared to water (for example, Litvak and Trippel, 1998;Turner and Montgomerie, 2002;Rosengrave et al, 2008;Galvano et al, 2013). The degree of stimulation of sperm velocity by the ovarian fluid is greatly explained by male-female interactions, which is indicative of the presence of CFC acting to promote gamete fusions of particular female-male combinations (Urbach et al, 2005;Rosengrave et al, 2008).…”
Section: Introductionmentioning
confidence: 99%